Políticas municipales y su incidencia en la promoción del desarrollo de las Micro y Pequeñas Empresas en el distrito de Chocope período: 2011 - 2014 - Muñoz Pretell, Juan Julio (2017)
ABSTRACT This research work is carried out with the objective of determining the situation and incidence of the Municipal Policies; Meeting the needs and demands of Micro and Small Enterprises, to jointly promote local development in the Chocope District. This is in accordance with article 73 of the Organic Law of Municipalities, which is; Provincial and district municipalities are responsible for promoting and promoting the planning process for the integral development corresponding to the scope of their province or district, gathering the priorities proposed in the processes of planning of local development of district character. Promote, permanently, the strategic coordination of comprehensive district development plans. Plans referring to the organization of the physical space and land use emitted by the district municipalities shall be subject to the provincial and district general plans and rules on the subject, establishing the specific functions of the provincial and district municipalities, among them, in With regard to development and local economy, should plan and provide infrastructure for local development. On the other hand is inherent the problem and influence of the knowledge of the obligations and tax benefits of Micro and Small Enterprises in their formalization, their difficulties in this process and the lack of orientation; Which determines their level of education, access to the information with which they counted, and many cumbersome obstacles to their organization and functioning that causes informality in 40% of the Mypes in the city of Chocope. In that sense, to reach the purpose of the investigation, the descriptive method of application character was used; Using interview techniques, surveys and documentary analysis; Achieving the hypothesis and objectives of research. The result of the present investigation allowed to conclude that the situation and incidence of the municipal policies for the promotion of the development of the MYPES by the District Municipality of Chocope have been implemented with the objective of generating their local development and the formalization of the MYPES; But it is not enough, since only in 2016 money was destined for S / .30, 000.00